Cyclic beta-amino acid derivatives: synthesis via lithium amide promoted tandem asymmetric conjugate addition-cyclisation reactions. - Davies, S; Díez, D; Dominguez, S; Garrido, N; Kruchinin, D; Price, P; Smith, A (2005)
The product distribution upon conjugate addition of homochiral lithium N-benzyl-N-alpha-methylbenzylamide to dimethyl-(E,E)-nona-2,7-dienedioate can be controlled to give either the cyclic 1,2-anti-1,6-anti-beta-amino ester (derived from conjugate addition and intramolecular enolate cyclisation) or the acyclic bis-beta-amino ester derivative (derived from double conjugate addition) in high de. The introduction of a protected nitrogen functionality into the diester skeleton facilitates, after conjugate addition and intramolecular enolate cyclisation, the asymmetric construction of piperidines in high de; variation in the N-protecting group indicates that the highest stereoselectivity is observed with alpha-branched N-substituents. Tandem conjugate addition-aldol reactions can also be achieved stereoselectively, with lithium amide conjugate addition to epsilon- and zeta-oxo-alpha,beta-unsaturated esters giving the corresponding five and six membered cyclic beta-amino esters in high de. N-deprotection by hydrogenolysis of the products arising from these reactions furnishes a range of polyfunctionalised transpentacin and transhexacin derivatives in high de and ee.